Dari Al-Khwarizmi hingga Al-Qur’an: Jejak Matematika dalam Warisan Intelektual Islam - Munhar; Surya Sari Faradiba (Mandalika Mathematics and Educations Journal, 2025)
The traces of mathematics in the Islamic intellectual heritage highlight Al-Khwarizmi's fundamental contributions and the mathematical implications of the Qur'an. This study analyzes the central role of Islamic civilization in preserving and developing mathematics, driven by both religious and practical motivations. A literature review method is used to synthesize data from various academic sources. The results show that Al-Khwarizmi revolutionized algebra and disseminated the Hindu-Arabic number system, forming the basis of modern algorithms. Furthermore, the Qur'an implicitly and explicitly contains mathematical concepts that inspire an understanding of divine order and its application in Islamic law. The conclusion affirms the symbiotic relationship between faith and reason in advancing mathematics in the Islamic world, providing a balanced perspective on global scientific progress